Unlocking Engagement: A Comprehensive Assessment of Student Involvement in High-Impact Practices - Schantz, April; Handley, Holley (Experiential Learning and Teaching in Higher Education, 2025)
The National Survey of Student Engagement (NSSE) project team was pivotal in creating a framework and gathering data on high-impact practices (HIPs) to enhance student engagement in learning nationwide. Student engagement in HIPs is a vital institutional performance metric closely linked to strategic objectives and state-level funding. To maximize NSSE results, we investigated our students' HIP engagement practices in-depth. We adapted NSSE items to enable department/college-level comparisons with the university-level NSSE report and intra-institution comparisons across units. A mixed methods approach included qualitative analysis to identify barriers to student HIP engagement. To obtain a representative sample, we employed diverse recruitment channels, such as the Dean of Students Office, Academic Engagement, and Student Affairs. Institutional comparisons revealed that the engagement of internships and capstone experiences aligned with NSSE findings. However, other HIP types deviated from NSSE expectations. Within-institution comparisons unveiled varying engagement patterns among college units, providing opportunities to recognize exemplary HIP engagement. Student-centric analyses identified four distinct classes of HIP engagement patterns, showcasing a diversity of approaches. Qualitative data analysis uncovered prominent obstacles to student involvement in HIPs, including time constraints, work-related conflicts, and limited awareness.